Larval settlement rate: A leading determinant of structure in an ecological community of the marine intertidal zone - Gaines, S. (1985)
Field studies demonstrate that the population structure of the barnacle Balanus glandula differs between locations of high and low larval settlement rate. These observations, together with results from a model for the demography of an open, space-limited population, suggest that the settlement rate may be a more important determinant of rocky intertidal community structure than is presently realized. Locations with a low larval settlement rate exhibit a generally low abundance of barnacles that varies slightly within years and greatly between years, reflecting yearly differences in settlement. Locations with a high-settlement rate exhibit a generally high abudance of barnacles. However, the abundance varies greatly within years with a significant oscillatory component (period, 30 weeks) and only slightly between years regardless of yearly differences in settlement. At the low-settlement location mortality of barnacles is independent of the area occupied by barnacles. At the high-settlement location mortality is cover-dependent due to increased predation by starfish on areas of high barnacle cover. In both locations the cover-independent component of mortality does not vary with age during the first 60 weeks. As assumed in the demographic model, the kinetics of larval settlement can be described as a process in which the rate of settlement to a quadrat is proportional to the fraction of vacant space within the quadrat. Generalizations that the highest species diversity in a rocky intertidal community is found at locations of intermediate disturbance, and that competition causes zonation between species of the barnacle genera Balanus and Chthamalus, seem to apply only to locations with high-settlement rates.